(untitled) (Research, Society and Development, 2021)
Background: Sickness absence represents a serious problem for industry and Social Security, since many of these workers become beneficiaries by the National Social Security Institute. The relationship between the factors that lead to dismissal and granting benefits to workers in the industry has yet to be studied. Objective: To determine the relationship between social and occupational factors to granting sickness benefits to industrial workers affected by Work-related Musculoskeletal Disorders. Methods: This is a retrospective cross-sectional with quantitative approach study involving industrial workers. The data contained in the evaluation form of workers who were admitted between 2016 and 2020 in a Reference Centers in Occupational Health were used. The data were descriptively evaluated and a logistic regression model was used to estimate the factors which are related to the type of assistance granted to the workers. Results: 108 medical records of industry workers were evaluated and 56.5% received the accident-related sickness assistance benefit (B-91). Most are workers from industry with light demand (95.4%), who perform repetitive work (93.5%), intense work pace (83.3%), with the shoulder being the region most frequently affected (85.2%). The factors that were significantly related to grating accidental-related sickness benefit: time in the current occupation (OR = 1.01), work involving cervical spine flexion (OR = 4.68), participation in the rehabilitation program (OR = 31.27) and referral to specialist consultations (OR = 3.10). Conclusion: The creation of institutional programs in the industry and the implementation of public health and social security policies are necessary to manage these factors.